Test of Teak Leaf Extract (Tectona Grandis) on Neuropharmacological Activity in Mice (Mus Muscullus) - Haryanto, Haryanto; Salsabila Febrianti Sahar; Aldya Marjannah Putri; Aril Baso; Femy, Femy; Intan Nurul Aini Syafri; Reski Annisa; Efra Tri Elya; Nur Rizky Aulia Fitri; Nabila Ayu Pratiwi (Sean Institute, 2025)
This study aims to comprehensively analyze the potential neuropharmacological activities of Tectona grandis leaf extract through laboratory tests and structured literature review of 21 relevant scientific articles. The review focuses on bioactive mechanisms associated with neuropharmacological parameters, including antioxidant, anti-inflammatory, analgesic, and neuroprotective activities, which relate to behavioral effect measurements such as PSM, SSSP, DSSP, SL, RO, PSL, and ANA commonly used in animal studies. The research method employed a systematic literature review involving structured searching, selection, data extraction, and synthesis of findings from national and international publications. The results indicate that Tectona grandis contains several active compounds, including flavonoids, phenolics, and anthraquinones, which contribute to reducing oxidative stress, inhibiting inflammation, and producing analgesic effects relevant to neuropharmacological mechanisms. Although direct assessments of neurobehavioral parameters are limited, mechanistic evidence highlights a significant potential for developing natural-compound-based therapies. The study concludes that Tectona grandis is a promising natural resource for further neuropharmacological research, particularly related to behavioral parameters and molecular pathways.